ANALISIS FAKTOR ANTESEDEN NIAT BELI KONSUMEN MEREK SKINCARE - Lukiman, Jessica Imanuela; Magdalena, Nonie (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2024)
This research seeks to examine the factors that contribute to consumer purchase intentions for skin care products. An investigation into forms of communication media, namely advertising and celebrity endorsements, which can increase brand awareness and ultimately impact purchase intentions was carried out. The questionnaire was distributed online in the form of a Google Form using a purposive sampling method. A total of 150 data were collected from respondents who were aware of celebrity advertisements supporting skin care products through multiple regression analysis. The research results show that there is a direct influence of advertising, celebrity endorsement, and brand awareness on consumer purchasing intentions, as well as an indirect influence, where brand awareness plays a role in mediating advertising and celebrity endorsement on consumer purchasing intentions. Companies can benefit from this research by formulating marketing communications tactics to increase their consumers' brand awareness, thereby driving increased consumer purchase intentions and gaining a competitive advantage over their competitors.